Delayed closure of complex defects with serial tightening of loop sutures – clinical outcome in 64 consecutive patients. (5th March 2013) - Felcht, Moritz; Koenen, Wolfgang; Weiss, Christel; Weina, Kasia; Geraud, Cyrill; Faulhaber, Jörg
Abstract Background Direct wound closure, flaps or grafts are considered to be gold standards for the reconstruction of defects. However, these techniques may not be applicable in all cases, especially for the challenging closure of large defects. Objective We developed a technique to close large defects, of varying size and shape, using serial tightening loop sutures. In 64 consecutive patients, loop sutures were applied to defects from 3 cm² up to 173 cm² for a maximum of 42 days with tightening every 2–7 days. Results The median size of the defects was 20 cm². In 58 patients (91%) the defects were closed by direct approximation of the wound edges within a median time of 11 days (range: 4–42 days). Two patients received a skin transplant after a significant reduction of the defect size and four remaining defects healed by secondary intention. The skin stretching of defects located on the trunk was faster compared with defects on the extremities. Defects located on the scalp were closed hair bearing with little scarring. Overall, aesthetic results were satisfying. Conclusion The use of loop sutures allows the delayed closure of large defects avoiding the need for skin flaps or grafts in most cases.